Charter Schools in Eight States Effects on Achievement, Attainment, Integration, and Competition - Zimmer, Ron (RAND Corporation, 2009)
Charter schools now exist in 40 states, but the best charter-school studies to date have focused on individual states. This book examines charter schools in eight states with varied policy contexts. It assesses the characteristics of charter schools' students, their effectiveness in raising student achievement and promoting graduation and college entry, and their competitive effects on student achievement in traditional public schools.